2007
DOI: 10.1111/j.1365-2222.2007.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐myeloperoxidase and anti‐cathepsin G antibodies in sulphonamide hypersensitivity

Abstract: These data indicate that anti-MPO antibodies and anti-cathepsin G antibodies are associated with sulphonamide HS. Anti-MPO antibodies have been shown to be pathogenic both in vitro and in vivo, leading to vasculitis lesions and vasculitis-like syndromes. The present study therefore suggests that vasculitis might be one mechanism of tissue damage in this sulphonamide HS. Furthermore, the evaluation of ANCA, and its relationship to disease severity and clinical outcome, should be considered in human patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…6A) and may or may not be the most relevant target in relation to agranulocytosis. In this regard, a recent study in dogs treated with sulfonamide, an aromatic amine drug, showed that anti-MPO and anti-cathepsin G antibodies were detected in sera (64).…”
Section: Discussionmentioning
confidence: 99%
“…6A) and may or may not be the most relevant target in relation to agranulocytosis. In this regard, a recent study in dogs treated with sulfonamide, an aromatic amine drug, showed that anti-MPO and anti-cathepsin G antibodies were detected in sera (64).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of delayed drug hypersensitivity is still not well understood . The ‘hapten hypothesis’ postulates that drugs have to bind to proteins to form potentially immunogenic protein–drug adducts .…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of delayed drug hypersensitivity is still not well understood . The ‘hapten hypothesis’ postulates that drugs have to bind to proteins to form potentially immunogenic protein–drug adducts . The ‘danger theory’ states that the immune system reacts in response to ‘danger’, such as cell death, oxidative stress or inflammation, rather than ‘foreignness’ …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hypersensitivity in dogs has been shown to be associated with antidrug, antimyeloperoxidase, and anti-cathepsin G antibodies [87,88]. It is thought that the immune reaction to sulfonamide is triggered by a reactive metabolite since sulfonamides are metabolized to hydroxylamines that may be further oxidized to nitroso derivatives, which in turn may form protein adducts, culminating in antibody-and/or cell-mediated immune responses [88]. A dog may be a very good mechanistic model for sulfonamide hypersensitivity in humans since this syndrome in dogs shares many similarities with that in humans.…”
Section: Sulfonamide-induced Hypersensitivitymentioning
confidence: 99%